Dinamika Kebebasan Berekspresi Aktivis di Era Digital: Perspektif HAM dan Pendidikan Kewarganegaraan - Anisah Dwi Indah Sari; Karyadi Hidayat; Siti Fatimah (Universitas Muhammadiyah Ponorogo, 2026)
Freedom of expression in the digital era faces various challenges, particularly for student activists who use social media to express criticism and encourage public participation. Previous studies have examined this issue from legal or digital literacy perspectives separately, while research integrating human rights and Civic Education remains limited. This study aims to analyze the dynamics of student activists’ freedom of expression in digital spaces and its implications for Civic Education. A qualitative approach was employed through semi-structured interviews with four University of Bengkulu students involved in student organizations. Data were analyzed using the Miles, Huberman, and Saldana model and validated through source and theory triangulation. The findings show that student organizations and social media serve as spaces for citizenship practice, supporting advocacy, public participation, and the expression of aspirations. However, participants still face intimidation, anonymous account attacks, doxing, and concerns regarding digital regulations that may create a chilling effect. The study also finds that digital literacy and communication ethics play an important role in promoting responsible freedom of expression. It concludes that Civic Education should strengthen digital citizenship competencies through digital literacy, critical thinking, ethical awareness, and an understanding of rights and responsibilities in digital spaces.